Anti-inflammatory and antibacterial activities of Lippia nodiflora and its effect on blood clotting time - Al-Snafi , Ali Esmail (University of Thi-Qar Journal of Science, 2013)
Aqueous extract of Lippia nodiflora possessed anti-inflammatory activity in Carrageenan induced mice paw edema in both doses 100 and 200 mg /kg bw (P< 0.01). However, the ethanolic extracts didn’t induced anti-inflammatory effects in both doses. Aqueous extract of Lippia nodiflora exerted a concentration – dependent antibacterial activity against E.coli but not effective against Staphylococcus aureus and Pseudomonas aeruginosa. Ethanolic extract possessed antibacterial activity against gram positive (Staphylococcus aureus) and gram negative (E. coli) but not effective against Pseudomonas aeruginosa. Ethanolic extract of Lippia nodiflora significantly hasten blood clotting when used in a dose of 100 mg/kg (P< 0.05) and 200 mg /kg (P< 0.01). The effect of the ethanolic extract appeared dose dependent. However, aqueous extract didn’t exerted significant effects on blood clotting time in both doses used in this sTUDY